![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(a,\dfrac{x}{4}=\dfrac{16}{128}\\ \Leftrightarrow128x=4.16\\ \Leftrightarrow128x=64\\ \Leftrightarrow x=\dfrac{1}{2}\)
Vậy...
\(b,1\dfrac{5}{6}=\dfrac{-x}{5}\\ \Leftrightarrow-6x=25\\ \Leftrightarrow x=-\dfrac{25}{6}\)
Vậy...
\(c,4,25:8=-3,5:x\\ \Leftrightarrow4,25x=-3,5.8\\ \Leftrightarrow x=-28:4,25\\ \Leftrightarrow x=-\dfrac{112}{17}\)
Vậy...
![](https://rs.olm.vn/images/avt/0.png?1311)
2, \(\Rightarrow\left\{{}\begin{matrix}\\\dfrac{5}{4}x-\dfrac{7}{2}=0\\\dfrac{5}{8}x+\dfrac{3}{5}=0\\\end{matrix}\right.\)
\(\Rightarrow\left\{{}\begin{matrix}x=\dfrac{14}{5}\\\\x=\dfrac{-24}{25}\\\end{matrix}\right.\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(a.\)
\(\dfrac{x}{4}=\dfrac{16}{128}\)
\(\Rightarrow x=\dfrac{16.4}{128}=\dfrac{1}{2}\)
\(b.\)
\(1\dfrac{5}{6}=-\dfrac{x}{5}\)
\(\Rightarrow\dfrac{11}{6}=-\dfrac{x}{5}\)
\(\Rightarrow x=\dfrac{11.\left(-5\right)}{6}=-\dfrac{55}{6}\)
\(c.\)
\(4,25:8=-3,5:x\)
\(\Rightarrow\dfrac{4,25}{8}=\dfrac{-3,5}{x}\)
\(\Rightarrow x=\dfrac{-3,5.8}{4,25}=-\dfrac{112}{17}\)
\(a)\dfrac{x}{4}=\dfrac{16}{128}\)
\(\Rightarrow\dfrac{16}{128}.4=\dfrac{1}{2}\)
\(b)1\dfrac{5}{6}=\dfrac{-x}{5}\)
\(\Rightarrow x=\dfrac{11}{6}.\left(-5\right)=\dfrac{-55}{6}\)
\(c)4,25:8=-3,5:x\)
\(\Rightarrow\dfrac{4,25}{8}=\dfrac{-3,5}{x}\)
\(\Rightarrow x=\dfrac{-3,5.8}{4,25}=\dfrac{-112}{17}\)
Chúc bạn học tốt!
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(\dfrac{x}{4}=\dfrac{16}{128}\Rightarrow x=\dfrac{4.16}{128}=\dfrac{1}{2}=0,5\)
b)\(1\dfrac{5}{6}=\dfrac{-x}{5}\\ \Leftrightarrow\dfrac{11}{6}=\dfrac{-x}{5}\Rightarrow-x=\dfrac{5.11}{6}=\dfrac{55}{6}\Rightarrow x=-\dfrac{55}{6}\)
c) \(\dfrac{4,25}{8}=\dfrac{-3,5}{x}\Rightarrow x=\dfrac{8.\left(-3,5\right)}{4,25}=-\dfrac{112}{17}\)
a,X/4=16/28
=»x/4=4/7
=4/7.4
=7
b,1/5/6=-x/5
-x/5=11/6
X=11/6.5
X=55/6
![](https://rs.olm.vn/images/avt/0.png?1311)
a)\(\dfrac{x}{4}=\dfrac{16}{128}\)
\(\Leftrightarrow\dfrac{x}{4}=\dfrac{1}{8}\)
\(\Rightarrow x=\dfrac{1.4}{8}=\dfrac{1}{2}\)
b)\(1\dfrac{5}{6}=\dfrac{-x}{5}\)
\(\Leftrightarrow\dfrac{11}{6}=\dfrac{-x}{5}\)
\(\Rightarrow-x=\dfrac{11.5}{6}=\dfrac{-55}{6}\)
c)\(4,25:8=-3,5:x\)
\(\Leftrightarrow\dfrac{17}{32}=\dfrac{-3,5}{x}\)
\(\Rightarrow x=\dfrac{\left(-3,5\right).32}{17}=-\dfrac{112}{17}\)
Tìm x
a)\(\dfrac{x}{4}\)=\(\dfrac{16}{128}\)
\(\Rightarrow\)x.128=16.4
x.128=64
x=64:128
x=\(\dfrac{1}{2}\)
Vậy x=\(\dfrac{1}{2}\)
b)\(1\dfrac{5}{6}\)=\(\dfrac{-x}{5}\)
\(\dfrac{11}{6}\)=\(\dfrac{-x}{5}\)
-x:5=\(\dfrac{11}{6}\)
-x=\(\dfrac{11}{6}\).5
-x=\(\dfrac{55}{6}\)
\(\Rightarrow\)x=\(\dfrac{-55}{6}\)
Vậy x=\(\dfrac{-55}{6}\)
c)4,25:8 = -3,5:x
-3,5:x=\(\dfrac{17}{4}\)
x=-3,5:\(\dfrac{17}{4}\)
x=\(\dfrac{14}{17}\)
Vậy x=\(\dfrac{14}{17}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
Câu a :
\(\dfrac{x}{4}=\dfrac{16}{128}\) \(\Leftrightarrow x.128=4.16\) \(\Rightarrow x=\dfrac{1}{2}\)
Câu b :
\(1\dfrac{5}{6}=-\dfrac{x}{5}\) \(\Leftrightarrow11.5=-x.6\) \(\) \(\Rightarrow-x=-\dfrac{55}{6}\)
Câu c :
\(\dfrac{4,25}{8}=\dfrac{-3,5}{x}\) \(\Leftrightarrow4,25.x=8.-3,5\) \(\Rightarrow x=-\dfrac{112}{17}\)
a,Ta có : x.128=16.4
x.128=64
Suy ra : x=1/2
b,\(1\dfrac{5}{6}=\dfrac{11}{6}\)
Ta có ; 11.5=-x.6
-x.6=55
Suy ra : x=-55/6
c,Ta có : 4,25.x=-3,5.8
4,25.x=-28
Suy ra : x=-112/17
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(x+\dfrac{1}{3}=\dfrac{3}{4}\Leftrightarrow x=\dfrac{3}{4}-\dfrac{1}{3}\Leftrightarrow x=\dfrac{5}{12}\) vậy \(x=\dfrac{5}{12}\)
b) \(x-\dfrac{2}{5}=\dfrac{5}{7}\Leftrightarrow x=\dfrac{5}{7}+\dfrac{2}{5}\Leftrightarrow x=\dfrac{39}{35}\) vậy \(x=\dfrac{39}{35}\)
c) \(-x-\dfrac{2}{3}=\dfrac{-6}{7}\Leftrightarrow x=\dfrac{-2}{3}+\dfrac{6}{7}\Leftrightarrow x=\dfrac{4}{21}\) vậy \(x=\dfrac{4}{21}\)
d) \(\dfrac{4}{7}-x=\dfrac{1}{3}\Leftrightarrow x=\dfrac{4}{7}-\dfrac{1}{3}\Leftrightarrow x=\dfrac{5}{21}\) vậy \(x=\dfrac{5}{21}\)
a) x + \(\dfrac{1}{3}\) = \(\dfrac{3}{4}\)
x = \(\dfrac{3}{4}\) - \(\dfrac{1}{3}\)
x = \(\dfrac{5}{12}\)
Vậy x = \(\dfrac{5}{12}\)
b) x - \(\dfrac{2}{5}\) = \(\dfrac{5}{7}\)
x = \(\dfrac{5}{7}\) + \(\dfrac{2}{5}\)
x = \(\dfrac{39}{35}\)
Vậy x = \(\dfrac{39}{35}\)
c) -x - \(\dfrac{2}{3}\) = \(-\dfrac{6}{7}\)
- x = \(-\dfrac{6}{7}\) + \(\dfrac{2}{3}\)
- x = \(-\dfrac{4}{21}\)
⇒ x = \(\dfrac{4}{21}\)
Vậy x = \(\dfrac{4}{21}\)
d) \(\dfrac{4}{7}\) - x = \(\dfrac{1}{3}\)
x = \(\dfrac{4}{7}\) - \(\dfrac{1}{3}\)
x = \(\dfrac{5}{21}\)
Vậy x = \(\dfrac{5}{21}\)
\(\dfrac{x+7}{130}+\dfrac{x+5}{128}+\dfrac{x-234}{111}=1\)
\(\left(\dfrac{x+7}{130}-1\right)+\left(\dfrac{x+5}{128}-1\right)+\left(\dfrac{x-234}{111}+1\right)=0\)
\(\dfrac{x-123}{130}+\dfrac{x-123}{128}+\dfrac{x-123}{111}=0\)
\(\left(x-123\right)\left(\dfrac{1}{130}+\dfrac{1}{128}+\dfrac{1}{111}\right)=0\)
\(x-123=0\) (do \(\dfrac{1}{130}+\dfrac{1}{128}+\dfrac{1}{111}>0\))
\(x=123\)